IoT-Enabled Ambulances Assisting Citizens' Well-Being after Earthquake Disasters in Smart Cities - Anagnostopoulos, Theodoros; Ntalianis, Klimis S.; Tsapatsoulis, Nicolas (My University, 2019)
Physical disasters can highly impact the well-being of people living in Smart Cities (SCs). Many citizens, including children and seniors, can face serious issues and survival risks after a physical disaster. Internet of Things (IoT) technology can be used to mitigate such risks by providing the technological solution to assist citizens in extreme situations. Such extreme physical disasters are earthquakes. In earthquakes houses and public buildings may collapse and capture many individuals in the ruins. Lives of citizens are seriously threatened. After an earthquake, in a hostile environment, ambulances should take control and provide solutions to fundamental human needs. In this paper an Emergency Medical Service (EMS) system is proposed, enabled with IoT technology. Our system incorporates, sensors and IoT equipment embedded to ambulances to assist and give solutions to peoples' problems after an earthquake. Specifically two use cases are examined and a dynamic routing algorithm is proposed to face the problem. The overall scheme is evaluated using synthetic data from the SC of Manchester, United Kingdom. Certain metrics are introduced to compare the proposed use cases in the context of the emerging SCs technological environments.
Keywords: Dynamic Routing; Earthquake Disaster; Heterogeneous Fleet Management; Internet of Things; Smart Cities